Investigating approaches to the treatment and preservation of a collection of Egyptian limestone funerary stelae. Issue 1 (3rd April 2018) - Roberts, Caroline; Davis, Suzanne L.; Gordon, LeeAnn Barnes; DeRoo, Cathy Selvius
ABSTRACT: This paper discusses the development of a treatment protocol and preservation guidelines for a collection of 211 limestone funerary stelae from the Roman Egyptian city of Terenouthis. The stelae, now at the University of Michigan's Kelsey Museum of Archaeology, suffer from surface powdering, soluble salt activity, stone delamination, biological staining, and a peeling, darkened nitrocellulose coating. Analytical techniques including FTIR, portable XRF, XRD, specimen culturing, and DNA analysis were used to characterize the stone, confirm the presence of soluble salts, identify the coating, and determine the exact nature of the biological growths seen on many stelae. These data were used to investigate treatment approaches, including consolidation, stone stabilization, coating reduction, and biostain reduction. Desalination by poultice was also explored. Based on the results of testing, a criterion-based treatment protocol was developed. The protocol recommends treatment steps including consolidation with CaLoSiL NP25 nanolime, structural stabilization using a variety of B-72 applications, and coating reduction with acetone in different solvent carriers. Finally, environmental monitoring and scientific analysis were used to create a set of environmental guidelines for the collection's long-term preservation.